Launch of Food Security Simulator - Kenya - Ecker, Olivier; Comstock, Andrew R. (Kenya Institute for Public Policy Research and Analysis, 2023)
Presented by Olivier Ecker, Senior Research Fellow, IFPRI and Andrew Comstock, Senior Research Analyst, IFPRI Launch of Food Security Simulator - Kenya KIPPRA Annual Regional Conference Kilifi, Kenya June 21, 2023